The Influence of the Glenn Doman Method on Social Interaction Ability of Children with Autism: A Quasi-Experimental Study - Reska Handayani; Ramaita Ramaita; Anggra Trisna Ajani; Indri Ramadini (Indonesian Journal of Global Health Research, 2024)
Autism is a spectrum disorder autism disorder (ASD) that experiences impaired social communication, repetitive behavior, very limited interests, and sensory behaviors that begin early in life. One of the methods used in autism intervention is the glenn doman method. This study aims to determine the influence of the gleen doman method on the social interaction ability of autistic children at SLB Autisma YPPA Padang City. The research method used is quasi-experimental with a one-group pretest and postest design. Assessment of children's Social Interaction skills using ATEC (Autism Treatment Evaluation Checkliest) observation sheets. The research was carried out in July-August 2023 with a sample of 15 people. The results of the statistical test obtained a value of 0.000, there was a significant difference between the social interaction of autistic children that there was an influence of the Glenn Doman Method on the social interaction of autistic children. The implementation of learning for children with autism using the gleen doman method needs support and motivation from all parties, both schools and families, so that the learning program can run continuously so that there is an increase in social interaction of children with autism.